Graded Modules which Satisfy the Gr-Radical Formula: S. Ebrahimi Atani, F. Esmaeili Khalil Saraei - Team, Support (Thai Journal of Mathematics, 2010)
Let G be a monoid with identity e, and R be a graded commutative ring. Here we study the graded modules which satisfy the Gr- radical formula. The main part of this work is devoted to extending some results from McCasland modules to Gr-McCasland modules.